Wednesday

April 16, 2014

April 16, 2014

Posted by **Jenn** on Tuesday, March 19, 2013 at 11:44am.

f(x)=-2x^2+4x+1

- Use completing the square to... -
**Reiny**, Tuesday, March 19, 2013 at 11:52amf(x)=-2x^2+4x+1

= -2(x^2 - 2x**+1 - 1**) + 1

= -2( (x-1)^2 -1) + 1

= -2(x+1)^2 + 3

you should be able to state the properties you are looking for from that.

**Related Questions**

Algebra 2 - Solve by completing the square. aČ - 2√(3a) + 2 = 0 Solve for ...

maths - Consider the equation x(square) + 4px + 2q = 0 where p and q are real ...

Completing the square - Please show the procedure for answering this quadratic ...

Algebra 2 - Completing the square method allows you to solve any quadratic ...

Math - Hi everyone. Would someone be able to help me with this problems? I know ...

Precalc - use completing the square to describe the graph of each function. How ...

Algebra - Completing the square method allows you to solve any quadratic ...

maths - solve the following equation by completing the square x(square) - 4(...

Algebra - Can 2x^2+5x+10=0, be factored? If not, how do use, completing the ...

math - If I use the method of completing the square on 3w^2-4w+1=0 How would I ...